Metagenomics analysis of marine eukaryotic community in water and sediments at Lang Co - Da Nang sea by throughput 18S rRNA gene sequencing - Man, Tran Dinh; Thoa, Nguyen Kim; Viet, Nguyen Quoc; Minh, Phan Thi Tuyet; Ha, Pham Thanh; Thuy, Tran Thanh; Tu, Hoa Minh; Xuan, Le Thi Thanh; Mai, Bui Thanh (Vietnam Journal of Marine Science and Technology, 2021)
The present study applied metagenomics to characterize the diversity and relative occurrence of eukaryotic organisms in the sea water (LC05.W and LCDN.W) and sediment (LC05.S and LCDN.S) samples collected at the Lang Co - Da Nang sea in two years 2016 and 2017. The marine DNA metagenomes from water and sediments were isolated and analyzed by using specific primer 18S V4: 528F-706R with the barcode for gene-based metagenomic approach. Total tags were 374,336 (92,864 in LC05.W; 95,742 in LCDN.W; 86,593 in LC05.S and 91,385 in LCDN.S samples) and clustered at a 97% similarity into 5,204 unique operational taxonomic units (936 in LC05.W; 1631 in LCDN.W; 2,259 in LC05.S and 1,631 in LCDN.S). The taxonomic profile obtained by comparison with SILVA SSU database showed predominance of the kingdom: Eukaryote domain (61% in LC05.W; 32% in LCDN.W; 43% in LC05.S and 69% in LCDN.S); Metazoa (26% in LC05.W; 22% in LCDN.W; 37% in LC05.S and 19% in LCDN.S). Fungi in samples collected in 2017 (31% in LCDN.W and 10% in LCDN.S) were dominant as compared to 2016 (6.0% in LC05.W and 0.6% in LC05.S). In addition, 0.4% and 10.0% in water and 19% and 2% in sediment sequences were unclassified. Protalveolata, Annelida, Chlorophyta, Nematoda, Arthropoda, Rotifera, Ascomycota, Diatomea were top ten at the phylum level in Lang Co - Da Nang sea water and sediments. The abundance distribution of 35 dominant genera among all samples was displayed in the species abundance heatmap. The taxonomic assignment based on 18S ribosomal sequences with the SSU base possibly showed the presence of eukaryotic species (191 in LC05.W; 320 in LC05.S; 278 in LCDN.W and 207 in LCDN.S) in the marine water and sediments collected at Lang Co - Da Nang sea.